PENINGKATAN EMPOWERMENT (PEMBERDAYAAN) PEREMPUAN MELALUI KELAS HYPNOPRENATAL PADA IBU HAMIL - Suryaningsih Suryaningsih; Rodiyatun Rodiyatun; Moh. Choirin Moh. Choirin; Kharisma Kusumaningtyas (UNUSA Press, 2019)
Anxiety will affect the client in facing pregnancy and labor/childbirth which will affect the mother's pain. There is no midwife in the working area of Puskesmas Socah Bangkalan ​​ that provides holistic services. Hypnoprenatal is programming client's subconscious mind as an effort to prepare for labor using a hypnosis technique that aims to make the delivery process safe, comfortable and enjoyable. The hypnoprenatal class targets 21 pregnant women in trimester 2 and 3 in the working area of Puskesmas Socah. This class is held 5 times with each 60 – 90 minute hypnoprenatal session. Activities carried out during the hypnoprenatal class include Pregnancy Examination, Hypnoprenatal Practice, Anchor (Anchoring), Pregnancy Exercise / Prenatal Yoga, and Complaint Overcoming. Overall, pregnant women in the second and third trimesters have no contraindications for hypnoprenatal act or antenatal yoga. All pregnant women participated in activities which was relaxed and comfortable. The results of the recapitulation of the pre and post hypnoprenatal questionnaires is that all mothers could overcome anxiety and feel more calm in living pregnancy, and feel better prepared for labor. Overall, pregnant women say they have repeated previous anchors. It is expected that all midwives can provide antenatal care holistically by adding hypnoprenatal services so that pregnant women can improve their ability to manage their own physical and psychological conditions in undergoing pregnancy and labor.